Thermal shock resistant phosphate cement-based steel structure coating and construction method thereof

By using a double-layer gradient structure design, a self-healing agent and a heat-resistant phase change material in the magnesium phosphate cement-based coating, the problems of insufficient durability and thermal shock resistance of the coating in high-temperature environments are solved, achieving high efficiency and Economical coating performance improvement.

CN119331444APending Publication Date: 2025-01-21浣江实验室 +1

Patent Information

Application Number
CN202411443177.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The existing magnesium phosphate cement-based coatings have problems of insufficient durability and thermal shock resistance in high temperature environments, and are complex in construction and high in cost.

Method used

It adopts a double-layer gradient structure design and combines self-healing agents and heat-resistant phase change materials to form a dense phosphate cement-based coating. The base coating improves density by adding inorganic fillers, and the reinforced surface layer introduces fiber reinforcement materials and self-healing microcapsules to enhance crack resistance and self-healing capabilities.

Benefits of technology

It significantly improves the durability and thermal shock resistance of the coating in high-temperature environments, has excellent self-healing capabilities, extends the service life of the coating, simplifies the construction process, and reduces costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119331444A_ABST
    Figure CN119331444A_ABST
Patent Text Reader

Abstract

The invention discloses a thermal shock resistant phosphate cement-based steel structure coating, which comprises: a bottom coating, which comprises 80-90 parts of potassium magnesium phosphate cement, 5-10 parts of an inorganic filler, 0.5-2.0 parts of an antifoaming agent, 1.0-3.0 parts of a high temperature resistant auxiliary agent, and 0.5-1.5 parts of reinforced fibers; and the reinforced surface layer is coated on the outer side of the bottom coating and comprises 60-70 parts of potassium magnesium phosphate cement, 5-10 parts of an inorganic salt phase change material, 5-15 parts of a fiber reinforced material, 2.0-5.0 parts of a repairing agent, 0.8-1.5 parts of a fire-resistant additive and 10-20 parts of lightweight aggregate. The invention further discloses a construction method of the thermal shock resistant phosphate cement-based steel structure coating. The phosphate cement-based coating is formed by combining a double-layer gradual change structure, the self-repairing agent and the heat-resistant phase change material, the durability and thermal shock resistance of the coating in a high-temperature environment can be remarkably improved, meanwhile, the excellent self-repairing capacity is achieved, and the service life of the coating is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials, and in particular relates to a thermal shock-resistant phosphate cement-based steel structure coating and a construction method thereof. Background Art

[0002] Steel structures are widely used in high-rise buildings, large-span structures and industrial facilities due to their high strength, light weight and excellent seismic resistance. However, in high temperature environments or frequent temperature changes, the mechanical properties of steel are easily affected, especially when the temperature rises to 300-500℃, the strength of steel will drop significantly, which can easily lead to structural failure. Therefore, for the protection of steel structures, protective coatings that are resistant to high temperatures, corrosion and have excellent bonding properties are particularly important.

[0003] Magnesium phosphate cement-based materials (MPC) have received extensive attention in the field of steel structure protection due to their fast curing, high strength, high temperature resistance and corrosion resistance. MPC materials form dense phosphate gels through the reaction of magnesium oxide and phosphates, which can form good adhesion with the surface of steel structures, thereby providing effective anti-corrosion protection. In addition, the passivation film generated by the phosphate system on the surface of steel further improves its anti-corrosion performance.

[0004] Patent CN114891381A proposes a magnesium phosphate cement-based anticorrosive fireproof coating for steel structures. By using ingredients such as dead-burned magnesium oxide, phosphates, and polyvinyl alcohol, a coating with excellent anticorrosion and fireproof properties is prepared. The coating exhibits good stability in high temperature environments, but its thick structure adds a large amount of lightweight thermal insulation materials such as expanded perlite and vermiculite, which affects its long-term durability. Patent CN202310704168.X introduces a fireproof thermal insulation coating, which includes an anticorrosive primer and a fireproof topcoat, both of which use magnesium phosphate materials as the main adhesive to improve the comprehensive protective performance of the coating through interlayer synergy. This solution optimizes the high temperature resistance and adhesion of the coating, and is particularly suitable for the protection of steel structures in high temperature environments. However, at the same time, there are differences in the thermal expansion coefficients between different coatings, which can easily lead to interlayer peeling during thermal shock, thereby reducing the overall protective effect of the coating. Patent CN202311216491.9 proposes a high heat flux resistant intumescent fire retardant coating, in which the primer coating is mainly composed of phosphate materials. By adding refractory fibers and flame retardants, the coating expands rapidly at high temperatures to form a thick insulation layer, which can effectively protect the steel structure from damage by high temperature thermal radiation. Although the coating exhibits excellent fire retardant properties at high temperatures, it has high requirements for mechanical strength and long-term durability. Under frequent temperature changes, the expansion layer is prone to lose its protective effect due to shrinkage and cracking, thereby affecting the service life of the coating. Patent CN202410501416.5 discloses a magnesium phosphate cement-based anticorrosion and anti-seepage coating material, which improves the waterproof and anti-seepage properties of the coating by introducing nano-modified magnesium oxide and phosphate, and further enhances the anti-corrosion effect of the coating by adding hydrophobic and anti-seepage layer materials. Although this nano-modification technology improves the anti-corrosion and anti-seepage properties of magnesium phosphate cement-based materials, its high material cost and complex multi-layer structure design limit the economic feasibility of its large-scale application.

[0005] Overall, the existing technical solutions have improved the anti-corrosion and high temperature resistance of magnesium phosphate cement-based coatings to a certain extent, but there are still some limitations in practical applications. First, the thick structure of the coating often leads to a high porosity, which makes it easy for moisture and corrosive media to penetrate, making it difficult to maintain the anti-corrosion effect for a long time. Secondly, although the multi-layer structure design improves the protective performance of the coating, its construction is complicated and it is easy to cause interlayer delamination in a thermal shock environment. Third, although the intumescent coating has good fire resistance at high temperatures, frequent temperature changes may cause it to crack and fail. In addition, the nano-modification method improves the density and durability of the coating, but due to its high cost, it limits its application in a wider range of fields. Summary of the invention

[0006] In order to overcome the deficiencies of the prior art, the present invention provides a thermal shock resistant phosphate cement-based steel structure coating and a construction method thereof, which has excellent high temperature resistance, corrosion resistance and self-repairing capabilities.

[0007] The technical solution adopted by the present invention to solve the technical problem is: a thermal shock resistant phosphate cement-based steel structure coating, comprising:

[0008] The base coating comprises 80-90 parts of potassium magnesium phosphate cement, 5-10 parts of inorganic filler, 0.5-2.0 parts of defoamer, 1.0-3.0 parts of high temperature resistant additive, and 0.5-1.5 parts of reinforcing fiber;

[0009] The reinforced surface layer is coated on the outside of the base coating, and includes 60-70 parts of potassium magnesium phosphate cement, 5-10 parts of inorganic salt phase change material, 5-15 parts of fiber reinforcement material, 2.0-5.0 parts of repair agent, 0.8-1.5 parts of refractory additive, and 10-20 parts of lightweight aggregate.

[0010] The present invention proposes a phosphate cement-based coating that combines a double-layer gradient structure, a self-healing agent and a heat-resistant phase change material, which can significantly improve the durability and thermal shock resistance of the coating in a high temperature environment, while having excellent self-healing ability to extend the service life of the coating.

[0011] Furthermore, the potassium magnesium phosphate cement is composed of magnesium oxide and composite phosphate, and the magnesium oxide is subjected to high-temperature calcination treatment, and the composite phosphate includes potassium dihydrogen phosphate and disodium hydrogen phosphate, and the mass ratio of potassium dihydrogen phosphate to disodium hydrogen phosphate is 1:0.2-0.3. Magnesium oxide is dead-burned magnesium oxide that has been subjected to high-temperature calcination treatment, ensuring that it has high purity and stability; potassium dihydrogen phosphate can not only provide the necessary phosphorus element, but also improve the early strength of cement; and disodium hydrogen phosphate plays an important role in adjusting the pH value of the coating and improving durability. The use of this composite system can effectively improve the adhesion and hydrolysis resistance of phosphate cement, ensuring excellent performance in high temperature and humid environments.

[0012] Furthermore, the inorganic filler includes nano-SiO 2 , quartz sand, and kaolin, the nano-SiO 2 The particle size of nano-SiO is 20-50 nanometers, the particle size of quartz sand is 100-200 mesh, and the particle size of kaolin is 200-400 mesh. 2 The particle size selection can effectively fill the tiny pores in the coating, improve the density and anti-permeability of the coating; the particle size selection of quartz sand has high compressive strength and wear resistance, which can enhance the overall structural stability of the coating; kaolin can increase the ductility and crack resistance of the coating, and is suitable for improving the construction performance of the coating.

[0013] Furthermore, the reinforcing fiber is one or two or more of carbon fiber, basalt fiber, glass fiber or aramid fiber, wherein the fiber diameter is 5-15 microns and the length is 3-15 mm. When the reinforcing fiber is carbon fiber and basalt fiber at the same time, the mass ratio of the two is 1:1.5, which can maintain the toughness of the coating while enhancing its crack resistance.

[0014] Furthermore, the inorganic salt phase change material is sodium chloride or calcium chloride, which can absorb and release heat during the phase change process, thereby effectively regulating the temperature fluctuation of the coating and improving the thermal stability and thermal shock resistance of the coating.

[0015] Furthermore, the repairing agent is a microcapsule encapsulating a sodium silicate solution, and the diameter of the microcapsule is 50-200 microns.

[0016] Furthermore, the shell material of the microcapsule is one of polyurethane, polyvinyl alcohol or phenolic resin, and the thickness of the shell is 1-5 microns; the mass fraction of the sodium silicate solution is 5-15%. The microcapsule contains a sodium silicate solution with a mass fraction of 5-15%. When the coating produces microcracks due to mechanical damage or environmental stress, the crack expansion will cause the microcapsule to rupture. The encapsulated sodium silicate solution and other repair agents are released from the microcapsule and flow into the crack area. Through the diffusion and gelation of the sodium silicate solution, the cracks are filled and sealed, thereby realizing the self-repair of the coating.

[0017] Furthermore, the refractory additive is composed of aluminosilicate, aluminum tripolyphosphate, aluminum silicate fiber and expanded graphite. The particle size of the aluminosilicate is 200-400 mesh, and the mass ratio of aluminum oxide to silicon oxide is 1:3-1:5; the particle size of the aluminum tripolyphosphate is 100-200 mesh, and the mass ratio of phosphorus is 30-40%; the diameter of the aluminum silicate fiber is 5-10 microns, and the length is 10-30 mm; the particle size of the expanded graphite is 30-100 microns, and the density is 100-150 kg / m 3 Refractory additives can release moisture at high temperatures and play a role in heat insulation and fire prevention. By rationally configuring these refractory additives and their parameters, the fire resistance and overall stability of phosphate cement-based coatings can be effectively improved to ensure their reliability in high temperature environments.

[0018] Furthermore, the lightweight aggregate is composed of expanded glass microspheres, expanded bauxite, ceramic microspheres and quartz microspheres; wherein the particle size of the expanded glass microspheres is 30-300 microns and the density is 50-200 kg / m 3 , thermal conductivity is 0.045-0.060W / (m·K); the particle size of the expanded bauxite is 0.5-2.0mm, and the density is 150-250kg / m 3, thermal conductivity is 0.065-0.075W / (m·K); the particle size of the ceramic microbeads is 100-500 microns, and the density is 150-300kg / m 3 , thermal conductivity is 0.060-0.080W / (m·K); the particle size of the quartz microbeads is 10-200 microns, and the density is 100-200kg / m 3 , thermal conductivity is 0.055-0.065W / (m·K). Lightweight aggregates in coatings can effectively reduce density, improve thermal insulation performance, and enhance the stability of coatings in high temperature environments.

[0019] The present invention also discloses a construction method of a heat shock resistant phosphate cement-based steel structure coating, which is based on the above-mentioned heat shock resistant phosphate cement-based steel structure coating and comprises the following steps:

[0020] The microcapsules are prepared by in-situ polymerization method, and a sodium silicate solution with a certain mass concentration is prepared as the core repair agent solution. An appropriate amount of deionized water is added to the reactor, and a certain amount of emulsifier is added, and stirred to form a uniform emulsion. The pretreated sodium silicate solution is slowly dripped into the stirred reactor, and the dripping rate is controlled so that the sodium silicate solution forms uniformly dispersed small droplets in the aqueous phase. The monomer of the shell material is added, and the polymerization reaction is carried out under the condition of controlled temperature. The shell material forms a dense microcapsule shell on the surface of the sodium silicate solution droplets through interfacial polymerization reaction. After the polymerization reaction is completed, the solution in the reactor is continued to be stirred so that the microcapsules are gradually solidified and form a shell. The reaction solution is filtered using a filter membrane to collect the generated microcapsules. The microcapsules are washed with deionized water several times to remove unreacted materials and impurities. The washed microcapsules are placed in a vacuum drying oven and dried to constant weight at 40-60°C to obtain a dry repair agent.

[0021] The potassium magnesium phosphate cement and the inorganic filler are fully mixed, and then the high temperature resistant additive and the reinforcing fiber are added in sequence, and stirring is continued to ensure uniform distribution. Finally, water is gradually added, and the amount of water is controlled at 20%-30% of the total mass of the solid material (that is, the water-cement ratio is 0.2-0.3) until a uniform slurry is formed. After mixing evenly, it is sealed and packaged as component A of the primer layer for standby use;

[0022] The potassium magnesium phosphate cement and the inorganic salt phase change material are fully mixed, and then the repair agent, the fiber reinforcement material and the refractory additive are added in sequence, and stirring is continued to ensure uniform distribution. Finally, water is gradually added, and the amount of water is controlled at 20%-30% of the total mass of the solid material (that is, the water-cement ratio is 0.2-0.3) until a uniform slurry is formed. After mixing evenly, it is sealed and packaged as component B of the primer layer for standby use;

[0023] Remove dust, rust and dirt from the surface of the steel structure to ensure the surface is clean;

[0024] On the treated steel substrate, the primer of component A is evenly applied to the surface of the steel structure by spraying or scraping, and the coating thickness is controlled at 1.0-3.0mm. After coating, it is cured at room temperature for 4-6 hours;

[0025] On the treated steel substrate, use spraying or scraping to evenly apply the primer slurry of component A to the surface of the steel structure. The coating thickness is controlled at 1.0-3.0mm. After coating, cure at room temperature for 4-6 hours;

[0026] Apply multiple times to ensure that the overall coating thickness reaches 2.0-6.0mm.

[0027] Potassium magnesium phosphate cement, inorganic filler, defoamer, high temperature resistant additive and reinforcing fiber are stirred and mixed for 3-5 minutes and sealed to be used as component A of the base coating; inorganic salt phase change material, repair agent, fiber reinforcement material and fire resistant additive are stirred and mixed for 3-5 minutes and sealed to be used as component B of the reinforced surface layer. The preparation method is relatively simple.

[0028] Through the above steps, the heat-shock-resistant phosphate cement-based steel structure coating of the present invention can effectively provide anti-corrosion, high-temperature resistance and self-repairing functions, and is suitable for the protection needs of various steel structures.

[0029] In view of the problems of the prior art, especially the shortcomings of the existing magnesium phosphate cement-based coating in terms of corrosion resistance and high temperature resistance, as well as the problems of complex construction, long cycle, weak adhesion between layers and poor volume stability of the existing coating system, the present invention proposes a heat shock-resistant phosphate cement-based steel structure coating, which optimizes the material ratio and structural design, takes potassium magnesium phosphate cement as the main film-forming material, combines double-layer gradient structure and self-repairing technology, and prepares a coating system that adapts to high temperature and frequent temperature changes. The coating system includes a dense base coating and a reinforced top coating. The base coating improves its density and adhesion by adding an appropriate amount of inorganic filler, and the reinforced surface layer enhances its crack resistance and self-repairing ability by introducing fiber reinforcement materials and self-repairing microcapsules. These fiber reinforcement materials not only improve the crack resistance and toughness of the coating, but also effectively improve the overall structural stability of the coating. The prepared coating has the characteristics of room temperature curing, simple construction, good volume stability, and strong adhesion to the steel substrate. It not only significantly improves the durability and stability of the coating in a high temperature environment, but also has good environmental protection performance and broad market application prospects.

[0030] The heat-shock-resistant phosphate cement-based steel structure coating of the present invention shows significant advantages in solving many deficiencies in the prior art. First, the double-layer gradient structure design of the coating not only enhances the adhesion and overall structural stability of the coating, but also improves the durability of the coating in high temperature and frequent temperature change environments. The base coating improves density and permeability resistance by adding inorganic fillers, while the fiber reinforcement materials and repair agents introduced into the reinforced surface layer effectively improve the crack resistance and self-repairing ability of the coating, ensuring that the coating can quickly restore its function when damaged.

[0031] The principle of adding the repair agent in the present invention is based on a variety of chemical reactions. When microcracks appear in the coating, the sodium silicate solution interacts with the unreacted phosphate material to promote the hydration reaction and form a dense phosphate gel, thereby enhancing the strength of the crack area. At the same time, the polymer in the shell material of the repair agent is cured at high temperature in the crack, and combines with the surrounding materials through polymerization reaction to form a new cross-linked structure, thereby restoring the integrity of the coating. In addition, the formation of microcracks may promote the formation of new crystals, and the released repair agent reacts with the phosphate material to help reform the crystal structure, fill the cracks and improve the crack resistance. The ions in the repair agent may also undergo ion exchange with other components in the coating, further enhancing the bonding strength and stability of the coating.

[0032] The prepared coating has the characteristics of curing at room temperature, the construction process is simple, the construction period is shortened, and the requirements for the construction environment are reduced. This efficient construction method not only reduces labor costs, but also improves construction safety. At the same time, the preferred potassium magnesium phosphate cement and its composite system ensure the excellent performance of the coating in high temperature and humid environments, greatly enhancing its reliability in practical applications.

[0033] The inorganic salt phase change material introduced in the present invention can absorb and release heat in a high temperature environment, thereby effectively regulating the temperature fluctuation of the coating, further improving its thermal stability and thermal shock resistance. Through the rational configuration of refractory additives and lightweight aggregates, the coating can effectively reduce density, improve thermal insulation performance, and enhance its stability in a high temperature environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 It is a schematic diagram of the coating maintenance process of the present invention.

[0035] Figure 2 It is a microscopic cross-sectional view of the primer layer and the reinforced surface layer in the coating of the present invention.

[0036] Figure 3 The apparent morphology of the coating in Example 1 of the present invention changes with the number of thermal shocks.

[0037] Figure 4 It is a schematic diagram of the coating (scratch) self-repairing effect of the present invention. DETAILED DESCRIPTION

[0038] In order to enable those skilled in the art to better understand the solutions of the present invention, the following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0039] Example 1

[0040] The present embodiment provides a heat shock resistant phosphate cement-based steel structure coating, wherein the components of the base coating are as follows by weight percentage: potassium magnesium phosphate cement: 85%, quartz sand (200 mesh): 5%, aluminum silicate powder (200 mesh): 3%, basalt fiber (average diameter 10 microns, average length 8 mm): 2%; the water-cement ratio is 0.25.

[0041] The components of the reinforced surface layer are as follows by weight percentage: potassium magnesium phosphate cement: 80%, calcium chloride (100 mesh): 5%, repair agent: 6%, carbon fiber: 4%, aluminum tripolyphosphate: 5%; the water-cement ratio is 0.2.

[0042] The powder components constituting phosphate cement are as follows by weight percentage: magnesium oxide (200-300 meshes, purity>88%): 65%, potassium dihydrogen phosphate (100-200 meshes): 25%, disodium hydrogen phosphate (100-200 meshes): 10%.

[0043] Preparation of repair agent: Prepare a sodium silicate solution with a mass concentration of 10%, add deionized water to the reactor, and add emulsifier polyethylene glycol (PEG), the mass ratio of which is 1% of the water phase. Start the stirring device, and control the stirring speed at 400rpm until the emulsifier is completely dissolved in the water to form a uniform emulsion. Slowly add the pretreated sodium silicate solution to the stirring water phase, and control the drop rate at 0.5mL / min to form uniformly dispersed droplets of the sodium silicate solution in the water phase. Maintain the stirring speed to ensure that the diameter of the droplets is in the range of 50-200 microns. After the sodium silicate solution is dispersed, slowly add the shell material to the reactor. Select a mixture of isocyanate and polyol as the shell material of the polyurethane, control the addition rate, and keep the reaction temperature at 40°C. Through interfacial polymerization, the shell material forms a dense microcapsule shell on the surface of the sodium silicate droplet. After the polymerization reaction is completed, continue to stir the solution in the reactor to gradually solidify the microcapsules, and the reaction time is 1-2 hours. Adjust the temperature of the reactor to 50°C to accelerate the curing process of the shell and ensure the mechanical strength of the microcapsules. Use a filter membrane to filter the solution after the reaction and collect the generated sodium silicate microcapsules. Wash the microcapsules with deionized water 3-4 times to remove unreacted shell materials and impurities. Place the washed microcapsules in a vacuum drying oven and dry them at 50°C for 12 hours until the microcapsules reach a constant weight state to obtain a dry repair agent.

[0044] First, put potassium magnesium phosphate cement and quartz sand into a dry powder mixer and stir for 2 minutes to ensure that the materials are fully mixed. Then add aluminum silicate powder and basalt fiber in turn and continue stirring for 2 minutes to ensure uniform distribution. Finally, gradually add water and continue stirring for 3 minutes until a uniform slurry is formed. After mixing evenly, seal and package it as component A of the base coating for later use.

[0045] Place potassium magnesium phosphate cement and calcium chloride in a dry powder mixer and stir for 2 minutes to ensure that the materials are fully mixed. Next, add the repair agent, carbon fiber and aluminum tripolyphosphate in sequence and continue stirring for 2 minutes to ensure uniform distribution. Finally, gradually add water and continue stirring for 3 minutes until a uniform slurry is formed. After mixing evenly, seal and package it as component B of the reinforced surface layer for later use.

[0046] S3. According to the standard steel structure surface treatment method, the steel structure surface is treated with dust, rust and dirt removal to ensure that the steel structure surface is clean and reaches SA2 level. Since phosphate-based materials are not sensitive to the humidity of the substrate, wet sandblasting method can be used during the treatment process.

[0047] S4. On the treated steel substrate, evenly apply the primer of component A to the surface of the steel structure by spraying or scraping. The coating thickness is controlled at 2.0mm. After coating, cure at room temperature for 4 hours to ensure the adhesion and anti-corrosion performance of the coating.

[0048] S5. On the treated steel substrate, use spraying or scraping to evenly apply the primer slurry of component A to the surface of the steel structure. The coating thickness is controlled at 2.0mm. After coating, cure at room temperature for 4 hours to ensure the adhesion and anti-corrosion performance of the coating.

[0049] After the coating is cured for 24 hours, a thermal shock test is performed on it. The coating sample is heated to 500°C and maintained for 10 minutes to ensure that the coating is fully heated. It is then taken out and placed in a room temperature environment for about 50 minutes to cool down, which is recorded as one thermal shock cycle. After different numbers of cycles, the coating surface is observed and recorded to determine the generation, expansion and self-healing effect of cracks. Figure 2 The surface appearance of the coating prepared in Example 1 during 60 thermal shock cycles is shown. The surface of the coating was smooth and crack-free before the thermal shock test, showing an initial good state. After 10 thermal shocks, slight cracks had appeared on the surface, but the cracks were relatively dispersed and the number of cracks was small, indicating that the coating began to be affected by the thermal shock. After 20 thermal shocks, the cracks began to increase and expand, and the cracks on the surface of the coating were more obvious, showing partial damage to the structure of the material after the thermal shock. After 30 thermal shocks, the cracks further expanded and the overall crack density increased, indicating that the coating had more stress concentration areas in repeated thermal shocks, and the material began to show greater thermal damage. After 40 thermal shocks, the cracks became more dense. After 50 thermal shock cycles, although the surface crack density was high, there was no further damage or peeling, indicating that the coating was still able to maintain structural integrity after repeated thermal shocks, indicating that its self-repair mechanism was working and avoiding serious structural damage.

[0050] After testing, its bonding strength reached 1.5MPa, and it remained intact without cracking after 60 thermal shock cycles at a high temperature of 500°C. The compressive strength reached 50MPa, and the open circuit potential was measured to be -0.2V vs SCE. The fire resistance limit of the coating exceeded 120 minutes.

[0051] Example 2

[0052] This embodiment provides a thermal shock-resistant phosphate cement-based steel structure coating, the weight percentage of the components of the base coating is: potassium magnesium phosphate cement: 88%, quartz sand: 4%, aluminum silicate powder: 2%, basalt fiber: 3%, and the water-cement ratio is 0.30. The weight percentage of the components of the reinforced surface layer is: potassium magnesium phosphate cement: 78%, potassium nitrate: 6%, repair agent (10% sodium silicate solution): 5%, glass fiber: 5%, aluminum tripolyphosphate: 6%, and water-cement ratio: 0.25. The weight percentage of the powder components constituting the phosphate cement is: magnesium oxide: 65%, potassium dihydrogen phosphate: 25%, and disodium hydrogen phosphate: 10%.

[0053] The preparation process is the same as that of Example 1. After testing, the bonding strength reaches 1.6MPa, remains intact without cracking after 50 thermal shock cycles at a high temperature of 500°C, the compressive strength reaches 45MPa, the open circuit potential is measured to be -0.3V vsSCE, and the fire resistance limit of the coating exceeds 90 minutes.

[0054] Example 3

[0055] This embodiment provides a heat shock resistant phosphate cement-based steel structure coating, the weight percentage of the components of the base coating is: potassium magnesium phosphate cement: 80%, kaolin: 7%, aluminum silicate powder: 4%, basalt fiber: 4%, and the water-cement ratio is 0.20. The weight percentage of the components of the reinforced surface layer is: potassium magnesium phosphate cement: 75%, sodium chloride: 8%, repair agent (15% sodium silicate solution): 6%, carbon fiber: 5%, aluminum tripolyphosphate: 5%, and the water-cement ratio is 0.30. The weight percentage of the powder components constituting the phosphate cement is: magnesium oxide: 65%, potassium dihydrogen phosphate: 25%, and disodium hydrogen phosphate: 10%.

[0056] The preparation process is the same as that of Example 1. After testing, the bonding strength reaches 1.5 MPa, remains intact without cracking after 60 thermal shock cycles at a high temperature of 500°C, the compressive strength reaches 43 MPa, the open circuit potential is measured to be -0.25 V vs SCE, and the fire resistance limit of the coating exceeds 100 minutes.

[0057] Example 4

[0058] This embodiment provides a heat shock resistant phosphate cement-based steel structure coating, the weight percentage of the components of the base coating is: potassium magnesium phosphate cement: 85%, quartz sand: 5%, aluminum silicate powder: 5%, aramid fiber: 5%, water-cement ratio is 0.25. The weight percentage of the components of the reinforced surface layer is: potassium magnesium phosphate cement: 80%, calcium chloride: 5%, repair agent (15% sodium silicate solution): 6%, basalt fiber: 5%, aluminum silicate powder: 4%, water-cement ratio is 0.25. The weight percentage of the powder components constituting the phosphate cement is: magnesium oxide: 65%, potassium dihydrogen phosphate: 25%, disodium hydrogen phosphate: 10%.

[0059] Prepare a sodium silicate solution with a mass concentration of 15%, add deionized water to the reactor, and add emulsifier polyethylene glycol (PEG), the mass ratio of which is 1% of the aqueous phase. Start a stirring device, and control the stirring speed at 400rpm until the emulsifier is completely dissolved in water to form a uniform emulsion. The pretreated sodium silicate solution is slowly added dropwise to the stirred aqueous phase, and the drop rate is controlled at 0.5mL / min, so that the sodium silicate solution forms uniformly dispersed droplets in the aqueous phase. Keep the stirring speed to ensure that the diameter of the droplets is within the range of 50-200 microns. After the dispersion of the sodium silicate solution is completed, slowly add the shell material to the reactor. Phenol and formaldehyde are gradually added to the reactor as a phenolic resin precursor. The molar ratio of phenol to formaldehyde is controlled at 1:1.2, while maintaining the reactor temperature at 60-80°C to promote the polycondensation reaction of the phenolic resin. The remaining preparation process is the same as Example 1.

[0060] After testing, its bonding strength reached 1.7MPa, and it remained intact without cracking after 45 thermal shock cycles at a high temperature of 500°C. The compressive strength reached 47MPa, and the open circuit potential was measured to be -0.28V vs SCE. The fire resistance limit of the coating exceeded 110 minutes.

[0061] Example 5

[0062] This embodiment provides a thermal shock-resistant phosphate cement-based steel structure coating, the weight percentage of the components of the base coating is: potassium magnesium phosphate cement: 82%, expanded perlite: 6%, aluminum silicate powder: 4%, glass fiber: 3%, and the water-cement ratio is 0.20. The weight percentage of the components of the reinforced surface layer is: potassium magnesium phosphate cement: 75%, sodium nitrate: 5%, repair agent (10% sodium silicate solution): 7%, carbon fiber: 5%, aluminum tripolyphosphate: 5%, and the water-cement ratio is 0.30. The weight percentage of the powder components constituting the phosphate cement is: magnesium oxide: 65%, potassium dihydrogen phosphate: 25%, and disodium hydrogen phosphate: 10%.

[0063] The preparation process is the same as that of Example 5. After testing, the bonding strength reaches 1.6MPa, remains intact without cracking after 55 thermal shock cycles at a high temperature of 500°C, the compressive strength reaches 46MPa, the open circuit potential is measured to be -0.27VvsSCE, and the fire resistance limit of the coating exceeds 100 minutes.

[0064] Example 6

[0065] This embodiment provides a thermal shock-resistant phosphate cement-based steel structure coating, the weight percentage of the components of the base coating is: potassium magnesium phosphate cement: 90%, quartz sand: 4%, aluminum silicate powder: 3%, basalt fiber: 3%, and the water-cement ratio is 0.20. The weight percentage of the components of the reinforced surface layer is: potassium magnesium phosphate cement: 85%, calcium chloride: 4%, repair agent (8% sodium silicate solution): 6%, glass fiber: 5%, aluminum tripolyphosphate: 5%, and the water-cement ratio is 0.25. The weight percentage of the powder components constituting the phosphate cement is: magnesium oxide: 65%, potassium dihydrogen phosphate: 25%, and disodium hydrogen phosphate: 10%.

[0066] The preparation process is the same as that of Example 4. After testing, the bonding strength reaches 1.7 MPa, remains intact without cracking after 50 thermal shock cycles at a high temperature of 500°C, the compressive strength reaches 48 MPa, the open circuit potential is measured to be -0.26 VvsSCE, and the fire resistance limit of the coating exceeds 105 minutes.

[0067] Example 7

[0068] This embodiment provides a thermal shock-resistant phosphate cement-based steel structure coating, the weight percentage of the components of the base coating is: potassium magnesium phosphate cement: 85%, kaolin: 6%, aluminum silicate powder: 4%, aramid fiber: 3%, and the water-cement ratio is 0.25. The weight percentage of the components of the reinforced surface layer is: potassium magnesium phosphate cement: 75%, calcium chloride: 6%, repair agent (10% sodium silicate solution): 6%, glass fiber: 5%, aluminum tripolyphosphate: 5%, and the water-cement ratio is 0.20. The weight percentage of the powder components constituting the phosphate cement is: magnesium oxide: 65%, potassium dihydrogen phosphate: 25%, and disodium hydrogen phosphate: 10%.

[0069] The preparation process is the same as that of Example 1. After testing, the bonding strength reaches 1.7 MPa, remains intact without cracking after 50 thermal shock cycles at a high temperature of 500°C, the compressive strength reaches 46 MPa, the open circuit potential is measured to be -0.28 VvsSCE, and the fire resistance limit of the coating exceeds 100 minutes.

[0070] Comparative Example 1

[0071] This comparative example provides a thermal shock-resistant phosphate cement-based steel structure coating. In order to verify the role of fiber reinforcement materials in coating performance, this comparative example removes the fiber reinforcement materials in the primer and topcoat. The other components and preparation process are the same as those in Example 1. The components of the primer are as follows by weight: potassium magnesium phosphate cement: 90%, quartz sand: 7%, aluminum silicate powder: 3%; the water-cement ratio is 0.20. The components of the reinforced surface layer are as follows by weight: potassium magnesium phosphate cement: 85%, calcium chloride: 4%, repair agent (8% sodium silicate solution): 6%, aluminum tripolyphosphate: 5%; the water-cement ratio is 0.25.

[0072] The powder components constituting phosphate cement are as follows by weight: magnesium oxide: 65%, potassium dihydrogen phosphate: 25%, and disodium hydrogen phosphate: 10%.

[0073] The preparation process is the same as that of Example 1. After testing, the bonding strength is 1.1 MPa, the surface shows obvious cracking after 30 thermal shock cycles at a high temperature of 500°C, the compressive strength is 40 MPa, the open circuit potential is measured to be -0.35 V vs SCE, and the fire resistance limit of the coating is 60 minutes.

[0074] Comparative Example 2

[0075] This comparative example provides a heat shock resistant phosphate cement-based steel structure coating. In order to investigate the role of self-healing microcapsules in the self-healing properties of the coating, this comparative example removes the repair agent in the reinforced surface layer. The other components and preparation process are the same as those in Example 8.

[0076] The components of the primer layer are as follows by weight: potassium magnesium phosphate cement: 85%, kaolin: 6%, aluminum silicate powder: 4%, aramid fiber: 5%; the water-cement ratio is 0.25.

[0077] The components of the reinforced surface layer are as follows by weight: potassium magnesium phosphate cement: 79%, calcium chloride: 8%, glass fiber: 8%, aluminum tripolyphosphate: 5%; the water-cement ratio is 0.20.

[0078] The powder components constituting phosphate cement are as follows by weight: magnesium oxide: 65%, potassium dihydrogen phosphate: 25%, and disodium hydrogen phosphate: 10%.

[0079] The preparation process is the same as that of Example 1. After testing, the bonding strength is 1.5 MPa, cracks extend on the surface after 25 thermal shock cycles at 500°C, but it does not fail completely, the compressive strength is 45 MPa, the open circuit potential is -0.30 V vs SCE, and the fire resistance limit of the coating is 60 minutes.

[0080] Compared with Example 1, after removing the self-repairing microcapsules, although the coating can still maintain a certain integrity after the thermal shock cycle, the cracks expand significantly, indicating that the coating without self-repairing function has weaker performance under thermal shock conditions. It can be seen that the presence of self-repairing microcapsules effectively extends the service life of the coating and improves its durability, especially when the cracks expand, it can play a self-repairing role and restore the structural integrity of the coating.

[0081] Comparative Example 3

[0082] This comparative example provides a thermal shock-resistant phosphate cement-based steel structure coating. In order to investigate the difference in the self-repairing performance of the coating between directly adding a sodium silicate solution and encapsulating the sodium silicate solution using self-repairing microcapsules, in this comparative example, a sodium silicate solution is directly added to the reinforced surface layer instead of encapsulating it in the form of microcapsules. The other components and preparation process are the same as those in Example 1.

[0083] The components of the base coat are as follows by weight: potassium magnesium phosphate cement: 85%, quartz sand: 7%, aluminum silicate powder: 5%, aramid fiber: 3%; the water-cement ratio is 0.25. The components of the reinforced surface layer are as follows by weight: potassium magnesium phosphate cement: 80%, calcium chloride: 5%, 8% sodium silicate solution (direct addition): 6%, glass fiber: 4%, aluminum tripolyphosphate: 5%; the water-cement ratio is 0.25.

[0084] The powder components constituting phosphate cement are as follows by weight: magnesium oxide: 65%, potassium dihydrogen phosphate: 25%, and disodium hydrogen phosphate: 10%.

[0085] Similar to Example 1, the base coating and the reinforcement surface layer are stirred and mixed according to a set ratio, and the sodium silicate solution is directly added to the reinforcement surface layer without microcapsulation. The coating is evenly applied to the surface of the steel structure according to the steps and cured.

[0086] After testing, its bonding strength is 1.3MPa. After 20 thermal shock cycles at 500℃, cracks expand on the coating surface, and larger cracks appear in some areas. The compressive strength is 42MPa. The open circuit potential is -0.32VvsSCE, and the fire resistance limit of the coating is 85 minutes.

[0087] Compared with the sodium silicate solution encapsulated in microcapsules, the performance of the sodium silicate solution directly added in this comparative example under thermal shock conditions is significantly worse. The directly added sodium silicate solution may partially react with the coating material during the coating formation process, resulting in its repair function not being effectively retained. When cracks appear, the directly added sodium silicate solution does not have a delayed release mechanism and cannot accurately release the repair agent for repair when cracks appear, as in the encapsulation form in the microcapsule, resulting in significantly poorer overall integrity and self-healing effect of the coating after thermal shock cycles.

[0088] It can be seen that the self-healing microcapsules effectively improve the self-healing function and durability of the coating by encapsulating the sodium silicate solution and ensuring that it is released only when the coating is damaged. Although it is simple to directly add the sodium silicate solution, it cannot fully exert its self-healing effect during the thermal shock process, and the effect is significantly inferior to the microcapsule form.

[0089] The above specific implementation modes are used to explain the present invention rather than to limit the present invention. Any modification and change made to the present invention within the spirit of the present invention and the protection scope of the claims shall fall within the protection scope of the present invention.

Claims

1. A thermal shock resistant phosphate cement-based steel structure coating, characterized in that: include: The base coating comprises 80-90 parts of potassium magnesium phosphate cement, 5-10 parts of inorganic filler, 0.5-2.0 parts of defoamer, 1.0-3.0 parts of high temperature resistant additive, and 0.5-1.5 parts of reinforcing fiber; The reinforced surface layer is coated on the outside of the base coating, and includes 60-70 parts of potassium magnesium phosphate cement, 5-10 parts of inorganic salt phase change material, 5-15 parts of fiber reinforcement material, 2.0-5.0 parts of repair agent, 0.8-1.5 parts of refractory additive, and 10-20 parts of lightweight aggregate.

2. The thermal shock resistant phosphate cement-based steel structure coating according to claim 1, characterized in that: The potassium magnesium phosphate cement is composed of magnesium oxide and composite phosphate, and the magnesium oxide is subjected to high-temperature calcination treatment. The composite phosphate includes potassium dihydrogen phosphate and disodium hydrogen phosphate, and the mass ratio of potassium dihydrogen phosphate to disodium hydrogen phosphate is 1:0.2-0.

3.

3. The thermal shock resistant phosphate cement-based steel structure coating according to claim 1, characterized in that: The inorganic filler comprises nano-SiO2, quartz sand, and kaolin. The particle size of the nano-SiO2 is 20-50 nanometers, the particle size of the quartz sand is 100-200 meshes, and the particle size of the kaolin is 200-400 meshes.

4. The thermal shock resistant phosphate cement-based steel structure coating according to claim 1, characterized in that: The reinforcing fiber is one or two or more of carbon fiber, basalt fiber, glass fiber or aramid fiber, wherein the fiber diameter is 5-15 microns and the length is 3-15 millimeters.

5. The thermal shock resistant phosphate cement-based steel structure coating according to claim 1, characterized in that: The inorganic salt phase change material is sodium chloride or calcium chloride.

6. The thermal shock resistant phosphate cement-based steel structure coating according to claim 1, characterized in that: The repairing agent is a microcapsule encapsulating a sodium silicate solution, and the diameter of the microcapsule is 50-200 microns.

7. The thermal shock resistant phosphate cement-based steel structure coating according to claim 6, characterized in that: The shell material of the microcapsule is one of polyurethane, polyvinyl alcohol or phenolic resin, and the thickness of the shell is 1-5 microns; the mass fraction of the sodium silicate solution is 5-15%.

8. The thermal shock resistant phosphate cement-based steel structure coating according to claim 1, characterized in that: The refractory additive is composed of aluminosilicate, aluminum tripolyphosphate, aluminum silicate fiber and expanded graphite. The particle size of the aluminosilicate is 200-400 meshes, and the mass ratio of aluminum oxide to silicon oxide is 1:3-1:5; the particle size of the aluminum tripolyphosphate is 100-200 meshes, and the mass ratio of phosphorus is 30-40%; the diameter of the aluminum silicate fiber is 5-10 microns, and the length is 10-30 mm; the particle size of the expanded graphite is 30-100 microns, and the density is 100-150 kg / m 3 .

9. The thermal shock resistant phosphate cement-based steel structure coating according to claim 1, characterized in that: The lightweight aggregate is composed of expanded glass microspheres, expanded bauxite, ceramic microspheres and quartz microspheres; wherein the particle size of the expanded glass microspheres is 30-300 microns and the density is 50-200 kg / m 3 , thermal conductivity is 0.045-0.060W / (m·K); the particle size of the expanded bauxite is 0.5-2.0mm, and the density is 150-250kg / m 3 , thermal conductivity is 0.065-0.075W / (m·K); the particle size of the ceramic microbeads is 100-500 microns, and the density is 150-300kg / m 3 , thermal conductivity is 0.060-0.080W / (m·K); the particle size of the quartz microbeads is 10-200 microns, and the density is 100-200kg / m 3 , the thermal conductivity is 0.055-0.065W / (m·K).

10. A construction method of a heat shock resistant phosphate cement-based steel structure coating, which is based on the heat shock resistant phosphate cement-based steel structure coating according to any one of claims 1 to 9, characterized in that: The following steps are included: The potassium magnesium phosphate cement and the inorganic filler are fully mixed, and then the high temperature resistant additive and the reinforcing fiber are added in sequence, and stirring is continued to ensure uniform distribution. Finally, water is gradually added, and the amount of water is controlled at 20%-30% of the total mass of the solid material until a uniform slurry is formed. After mixing evenly, it is sealed and packaged as component A of the primer layer for standby use; The potassium magnesium phosphate cement and the inorganic salt phase change material are fully mixed, and then the repair agent, the fiber reinforcement material and the refractory additive are added in sequence, and stirring is continued to ensure uniform distribution. Finally, water is gradually added, and the amount of water is controlled at 20%-30% of the total mass of the solid material until a uniform slurry is formed. After mixing evenly, it is sealed and packaged as component B of the primer layer for standby use; Remove dust, rust and dirt from the surface of the steel structure to ensure the surface is clean; On the treated steel substrate, the primer of component A is evenly applied to the surface of the steel structure by spraying or scraping, and the coating thickness is controlled at 1.0-3.0mm. After coating, it is cured at room temperature for 4-6 hours; On the treated steel substrate, use spraying or scraping to evenly apply the primer slurry of component A to the surface of the steel structure. The coating thickness is controlled at 1.0-3.0mm. After coating, cure at room temperature for 4-6 hours; Apply multiple times to ensure that the overall coating thickness reaches 2.0-6.0mm.

Citation Information

Patent Citations

  • High-heat-flow-resistant intumescent fireproof coating and preparation method thereof

    CN117126585A

  • A magnesium phosphate cement-based anticorrosion and anti-seepage coating material and its preparation method and application

    CN118063186B

  • Preparing method of high-temperature phase change heat storage material of core-shell structure

    CN106367035A

  • Phosphate cement based patching material and preparation method thereof

    CN107056225A

  • Microcapsule for self-repairing of cement-based micro-cracks and preparation method of microcapsule

    CN108383411A

Cited By

  • Chromium-free phosphate coating as well as preparation method and use method thereof

    CN119613992A

  • A chromium-free phosphate coating and its preparation method and use method

    CN119613992B

  • Polyurethane energy-saving door and window profile and preparation method thereof

    CN119704801A